Anterior dislocation of the shoulder with ipsilateral humerus shaft fracture - Pradhan, I; Banskota, AK (Kathmandu University Medical Journal, 2009)
Anterior dislocation of the shoulder joint with ipsilateral humerus shaft fracture is a very rare injury. Until July 2006 only 18 cases have been reported in the literature. Here we report a case of Anterior Shoulder dislocation with greater tuberosity and shaft of humerus fracture. The patient was treated by Open reduction and internal fixation of the shaft fracture followed by closed reduction of the dislocation. A post-operative rehabilitation program was instituted for complete rehabilitation of the shoulder function. Key words: Shoulder dislocation, Ipsilateral, Humerus, Fracture, Open reduction. doi: 10.3126/kumj.v6i4.1743 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 502-504